Reflections on consent in cord blood stem cell donation (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
After a rapid examination of practical profiles of the cord blood stem cell donation, the article analyses the Italian discipline, which in 2015 gave both parents the right to donate cord blood and placenta, deviating from the previously paradigm that designated the woman as the only one entitled to express the consent. Moreover, the paper will delve into an analysis that aim to identify the arguments for and against both theses on the ownership of consent, through a reflection that will go hand in hand with the identification of the title that legitimizes the subject to dispose of cord blood.
Keywords: Ownership of umbilical cord blood; stem cells; consent; body parts; operating room waste